If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4 = 6x + -1 Reorder the terms: 4 + x = 6x + -1 Reorder the terms: 4 + x = -1 + 6x Solving 4 + x = -1 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 4 + x + -6x = -1 + 6x + -6x Combine like terms: x + -6x = -5x 4 + -5x = -1 + 6x + -6x Combine like terms: 6x + -6x = 0 4 + -5x = -1 + 0 4 + -5x = -1 Add '-4' to each side of the equation. 4 + -4 + -5x = -1 + -4 Combine like terms: 4 + -4 = 0 0 + -5x = -1 + -4 -5x = -1 + -4 Combine like terms: -1 + -4 = -5 -5x = -5 Divide each side by '-5'. x = 1 Simplifying x = 1
| 5=0.6x+0.8 | | 1=4x-3x | | 5(2-x)+8x=3(x-6) | | 2x-1=7-2x | | J^2-26j+48=0 | | -6(2x+1)-14=10(x+2)-2x | | 11x^2-200x-400=0 | | -1+5x+4=2x+3x | | k+26=61 | | cos= | | -2x+5=3x | | 6+3/4(x-3)=8 | | -1+5x+4=2x+3+3x | | -2x+58=3x | | 2x-2+x+45=180 | | 3x^2+2=14 | | mL=3y+x | | 4x=12x^2 | | 3(4-a)+3(2-a)=5 | | 10-p=q | | 2x+1=3-2 | | 16h^2-9hk-25k^2=0 | | -6(x+5)-45=3-36 | | 10-2p=q | | 2x-4=7x+6 | | y=90-4c | | 4x+1-x=4 | | 360=2(4y+x-5)+3y+x+4x+y+10 | | 5x-1=3x-4 | | x+.875x=90 | | 8x^2-7x+4x-60-3=0 | | 2x+1=3x+3 |